SARS-CoV-2 spike protein binds to bacterial lipopolysaccharide and boosts proinflammatory activity. (9th December 2020) - Petruk, Ganna; Puthia, Manoj; Petrlova, Jitka; Samsudin, Firdaus; Strömdahl, Ann-Charlotte; Cerps, Samuel; Uller, Lena; Kjellström, Sven; Bond, Peter J; Schmidtchen,; Artur
Abstract: There is a link between high lipopolysaccharide (LPS) levels in the blood and the metabolic syndrome, and metabolic syndrome predisposes patients to severe COVID-19. Here, we define an interaction between SARS-CoV-2 spike (S) protein and LPS, leading to aggravated inflammation in vitro and in vivo . Native gel electrophoresis demonstrated that SARS-CoV-2 S protein binds to LPS. Microscale thermophoresis yielded a K D of ∼47 nM for the interaction. Computational modeling and all-atom molecular dynamics simulations further substantiated the experimental results, identifying a main LPS-binding site in SARS-CoV-2 S protein. S protein, when combined with low levels of LPS, boosted nuclear factor-kappa B (NF-κB) activation in monocytic THP-1 cells and cytokine responses in human blood and peripheral blood mononuclear cells, respectively. The in vitro inflammatory response was further validated by employing NF-κB reporter mice and in vivo bioimaging. Dynamic light scattering, transmission electron microscopy, and LPS-FITC analyses demonstrated that S protein modulated the aggregation state of LPS, providing a molecular explanation for the observed boosting effect. Taken together, our results provide an interesting molecular link between excessive inflammation during infection with SARS-CoV-2 and comorbidities involving increased levels of bacterial endotoxins.